The Taming of Education Evaluating Contemporary Approaches to Learning and Teaching - Creasy, Rob.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
This book evaluates contemporary approaches to education, with a particular focus on the ways in which assessment shapes the educational experience and influences pupils and students. It adopts a critical approach, arguing that there is a need for students to develop critical thinking skills, be flexible and have the capacity for originality. Education has increasingly come to be seen as a process with qualifications as the output; however, as economies change, attaining advantage increasingly relies on creativity and originality. Unfortunately, in the quest to remove uncertainty from education, creativity and originality are often overlooked; and the result is that education is impoverished. Creasy argues here that there is no single factor that has shaped education and led to this situation; rather, developments within education can be seen as having been shaped by a range of forces such as neoliberalism, New Public Management, standardization and internationalization. This is not to claim any deliberate undermining of education, but the cumulative effect is that education is less and less fit for purpose. Written for anyone involved in education, student, teacher or manager, this book draws upon Educations Studies, Sociology and Social Policy to offer a compelling critique of contemporary education.
Chapter 1. Seeing Education as a Process -- Chapter 2. Education: Wicked or Tame? -- Chapter 3. Control over Teachers: Taming Teachers -- Chapter 4. Shaping the Landscape of Education -- Chapter 5. Where We Learn -- Chapter 6. Education as a Process: Assessment, Outcomes and Achievement -- Chapter 7. Taming Assessment in Higher Education -- Chapter 8. Where Are We Now? -- Chapter 9. Towards Wicked Education.
Keywords: Education, Higher; Early childhood education; Educational Policy and Politics; Teaching and Teacher Education; Sociology of Education; Administration, Organization and Leadership; Higher Education; Early Childhood Education